Spatio-temporal changes in ecological vulnerability and its driving factors in western jilin, china in the last 30 years - Jiang, Haoxuan; Song, Chunwei; Han, Cheng; Du , Huishi (Bangladesh Journal of Botany, 2023)
In order to explore the quality of the ecological environment in the interlaced zone of agriculture and animal husbandry in western Jilin, this study used the vulnerability domain map evaluation model to select evaluation indicators based on GIS and RS technology. The principal component analysis method was used to carry out research on the ecological sensitivity of western Jilin from 1990 to 2020. Results showed that in terms of space-time distribution, severe and moderate vulnerability is mainly distributed in the northern part of the research area, and the moderate vulnerability area accounts for more than 73.13% of the area of the research area. From 2000 to 2020, the ecological vulnerability gradually decreased, and the overall ecological environment tended to improve, severe vulnerability is mainly distributed in unused land, and changes in different land types affect changes in ecological vulnerability, the ecological vulnerability in western Jilin has a strong correlation and is mainly located in the northern part of the research area. The area of high-high aggregation, hot spots and cold spots areas accounts for 1.84, 15.54 and 6.68% of the area of the research area, respectively. Bangladesh J. Bot. 52(2): 585-593, 2023 (June) Special